Improvement of Prospective Teacher Mathematics Reasoning Ability Using Numeration Assisted E-Learning - Jayanti, Jayanti; Jumroh, Jumroh (Universitas PGRI Madiun, 2021)
This study aims to examine the improvement of prospective teacher Mathematical Reasoning (KPM) abilities through E-Learning-assisted Numeration learning. This study used a quasi-experimental method with a non-equivalent pretest and posttest control group design. The subjects of this study were mathematics prospective teachers at Universitas PGRI Palembang. namely the experimental class which received E-learning assisted numeracy learning (PNBE) and the control class which received conventional learning (PK). Based on the results of the analysis of the difference in the mean difference in the KPM increase of prospective teachers who received PNBE learning and prospective teacher who received conventional learning, the scores from the table of increasing KPM of students who received E-learning-assisted Numeration learning (PNBE) were better than a prospective teacher who received conventional learning. Based on the results of data analysis, it can be concluded that numeracy skills and mathematical reasoning abilities of fourth-semester prospective teacher PGSD at PGRI university are quite good. It is recommended for teaching staff/lecturers to be able to try out this learning model on other mathematical abilities.